Effective elimination of harmonics on the part of chosen dc bus in dual active type converter - Janaki, N; R.Krishna Kumar, Dr (International Journal of Engineering and Technology, 2018)
In order to manage the flow of power in the dual bridge type converter, a modulation technique called phase shifted square wave is employed. As an outcome, increased range of ripples in current is resulted, and that further provokes the vibration in inductance and capacitance circuit. Due to this effect, there exists uncertainty in the value of current and voltage, failure of operating components and stress in the filter. To miti-gate the above ill effects, three level modulation can be done using three phase shift square wave control angles. These three angles now elimi-nate the harmonics in chosen DC link and the harmonic eliminating procedure is justified and simulated.Â Â